(untitled) (New Jersey, 2006)
Science, Society, and the Supermarket: The Opportunities and Challenges of Nutrigenomics discusses the many ethical, legal, and social challenges presented by nutrigenomics. Concerning itself with the basic uses of nutrigenomic research as well as its clinical and commercial aspects.
Keywords: Nutrition,Physiological genomics,Nutrient interactions,Dinh dưỡng,Sinh lý gen,Tương tác dinh dưỡng; Genetic aspects,Khía cạnh di truyền